Sentient flesh: thinking in disorder, poiēsis in black - Judy, R.A. (Black outdoors, 2020)
"In Sentient Flesh R. A. Judy takes up freedman Tom Windham's 1937 remark "we should have our liberty 'cause . . . us is human flesh' as a point of departure for an extended meditation on questions of the human, epistemology, and the historical ways in which the black being is understood. Drawing on numerous fields, from literary theory and musicology, to political theory, phenomenology, as well as Greek and Arabic philosophy, Judy engages literary texts and performative practices such as music and dance that express knowledge and conceptions of humanity appositional to those grounding modern racialized capitalism. Operating as critiques of Western humanism, these practices and modes of being-in-the-world-which Judy theorizes as "thinking in disorder," or "poiēsis in black"-foreground the irreducible concomitance of flesh, thinking, and personhood. As Judy demonstrates, recognizing this concomitance is central to finding a way past the destructive force of ontology that still holds us in thrall. Erudite and capacious, Judy's Sentient Flesh offers a major intervention into the black study of life"--